Productive researchers in countries with limited research capacity: Researchers as agents in post-Soviet Kazakhstan. (8th May 2017) - Kuzhabekova, Aliya; Mukhamejanova, Dinara
Abstract : Purpose: This study aims to explore how some researchers become successful in the research context of a transitional country despite the resource- and training-related limitations imposed by an immature research system. Design/methodology/approach: The research uses Unger's ideas within agency theory, specifically, his concepts of "negative capability" and "formative context" as its framework. The study adopts a descriptive qualitative approach, whereby the data collected from 19 in-depth interviews with successful researchers from various universities of Kazakhstan is analyzed using emergent thematic coding. Findings: The study findings are consistent with Unger's agency theory. The theory predicts that researchers can achieve their goals by adapting to the constrained context and can take steps to transform the context in desirable ways. Specifically, the Kazakhstani researchers have successfully adapted the Soviet mechanism of research schools to the new realities by "exploiting" a recently introduced government-funded mobility program for doctoral students for their own purposes. This mechanism is conductive to junior researchers' capacity building, as well as to increasing the productivity of the leading researchers and their research teams. Originality/value: The contribution of the study consists in the fact that it explores the process of researcher development, more specifically, individual level research capacity building in the context of a transitional post-Soviet country. The study pays special attention to the role of international mobility and research schools in the development of research skills. The conclusions of the paper are of interest to the scholars of researcher development in general and to the specialists in individual research capacity building in Eurasia in particular.